2013
DOI: 10.1073/pnas.1307637110
|View full text |Cite
|
Sign up to set email alerts
|

Organellar oligopeptidase (OOP) provides a complementary pathway for targeting peptide degradation in mitochondria and chloroplasts

Abstract: Both mitochondria and chloroplasts contain distinct proteolytic systems for precursor protein processing catalyzed by the mitochondrial and stromal processing peptidases and for the degradation of targeting peptides catalyzed by presequence protease. Here, we have identified and characterized a component of the organellar proteolytic systems in Arabidopsis thaliana, the organellar oligopeptidase, OOP (At5g65620). OOP belongs to the M3A family of peptidedegrading metalloproteases. Using two independent in vivo … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
104
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(110 citation statements)
references
References 58 publications
(62 reference statements)
4
104
0
Order By: Relevance
“…Organellar oligopeptidase (OOP) is another zinc metalloprotease that participates in targeting peptide degradation. OOP degrades peptides with lengths of eight to 23 amino acid residues but fails to act on folded proteins, consistent with its catalytic cavity size, as in the case of PreP1/2 (Kmiec et al, 2013(Kmiec et al, , 2014. The OOP-null mutant phenotype is wild type like, but genetic interaction with the prep1 prep2 double mutant is observed, indicating complementary functions for OOP and PreP1/2 (Kmiec et al, 2013).…”
Section: Processing Proteasesmentioning
confidence: 65%
See 2 more Smart Citations
“…Organellar oligopeptidase (OOP) is another zinc metalloprotease that participates in targeting peptide degradation. OOP degrades peptides with lengths of eight to 23 amino acid residues but fails to act on folded proteins, consistent with its catalytic cavity size, as in the case of PreP1/2 (Kmiec et al, 2013(Kmiec et al, , 2014. The OOP-null mutant phenotype is wild type like, but genetic interaction with the prep1 prep2 double mutant is observed, indicating complementary functions for OOP and PreP1/2 (Kmiec et al, 2013).…”
Section: Processing Proteasesmentioning
confidence: 65%
“…Transit peptides are 26 to 146 amino acids long (Zybailov et al, 2008). Structural and biochemical studies have reported that PreP1 degrades various peptide substrates of 10 to 65 amino acids (Moberg et al, 2003;Ståhl et al, 2005), whereas OOP cleaves peptide fragments ranging from eight to 23 amino acids (Kmiec et al, 2013). Consequently, both proteases are able to function in transit peptide degradation, with OOP acting in parallel or downstream to PreP.…”
Section: Sequential Proteolytic Events For Preprotein Processing and mentioning
confidence: 99%
See 1 more Smart Citation
“…Out of the various peptidases quantified, only the OOP peptidase was significantly affected (nearly 2-fold reduced levels) in clpf-1 ( Figure 3C; Supplemental Data Set 3). This M3 peptidase is thought to degrade cleavage products from upstream proteases, such as the Clp system or Prep1,2 (Kmiec et al, 2013;Nishimura and van Wijk, 2015).…”
Section: Loss-of-function Clpf Mutantsmentioning
confidence: 99%
“…Most mitochondrial proteins responsible for the machinery of respiration and metabolism are synthesized in the cytosol and imported into mitochondria. After import, N-terminal presequences containing targeting signals are cleaved from many proteins by the mitochondrial processing peptidase (MPP; Sjoling and Glaser, 1998;Zhang and Glaser, 2002), and the mitochondrial presequences themselves are then degraded by presequence peptidases (Ståhl et al, 2002;Moberg et al, 2003;Bhushan et al, 2005) and oligopeptidase (Kmiec et al, 2013). The specificity of the MPP cutting sites has been analyzed by comparison of the experimentally determined N-terminal sequences of mature proteins with the amino acid sequences of the precursor proteins.…”
mentioning
confidence: 99%